Characteristics and Outcomes of Stroke Patients Transferred to Hospitals Participating in the Michigan Coverdell Acute Stroke Registry. (May 2016) - Nickles, Adrienne V.; Roberts, Stacey; Shell, Erin; Mitchell, Marylou; Hussain, Syed; Lyon-Callo, Sarah; Reeves, Mathew J.
Abstract : Background—: Interhospital transfer of acute stroke patients is becoming increasingly important as regional stroke systems of care continue to evolve. We describe the characteristics and outcomes of stroke cases transferred to hospitals participating in the Michigan Coverdell Stroke Registry. Methods and Results—: Thirty-six hospitals participated in the Michigan registry during 2009 to 2011. Transfer patients were transferred from another hospital either acutely or after admission. Multivariable logistic regression was used to determine predictors of transfer and the independent association between transfer and in-hospital mortality and complications. Of 16 202 acute stroke admissions, 19.1% were transferred. Independent predictors of being transferred included younger age, hemorrhagic stroke, and higher stroke severity, but having a past history of stroke decreased the likelihood of being transferred. Transferred cases had higher in-hospital mortality (12.0% versus 6.4%; P <0.001) compared with regular admissions and were more likely to suffer complications (18.4% versus 12.8%; P <0.001). These differences remained after adjustment for confounding variables (adjusted odds ratio for mortality =1.32, 95% confidence interval 1.12, 1.56; adjusted odds ratio for complications =1.39, 95% confidence interval 1.22, 1.58). Among ischemic stroke, elevated odds of poor outcomes among transferred patients remained after adjustment for stroke severity. Conclusions—: Transferred patients represent a complex admixture of patient characteristics that result in higher risks of poor outcomes. Our results suggest that it is prudent to account for patient transfer status when comparing hospital outcomes and that stroke registries need to expand their data collection capacity to provide a better understanding of the relative benefits and risks of transferring patients.